2005
DOI: 10.1093/eurpub/cki108
|View full text |Cite
|
Sign up to set email alerts
|

Smoking by French general practitioners: behaviour, attitudes and practice

Abstract: This study examines smoking habits among French GP's, intervention practices, and opinions about their ability to help patients quit smoking. This study found a smoking prevalence rate of 32.1%, 33.9% of male physicians were smokers and 25.4% of women. This study found a smoking prevalence rate of 32.1%, 33.9% of male physicians were smokers and 25.4% of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
38
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 11 publications
6
38
0
1
Order By: Relevance
“…Besides, 84% of former smokers were men. Therefore, there was a trend in that there is a greater ratio of former smokers among the elderly male physicians, as it has been already shown in other studies 8,13 . Most of the ENTs who stopped smoking (74%) did it on their own.…”
Section: Discussionsupporting
confidence: 67%
“…Besides, 84% of former smokers were men. Therefore, there was a trend in that there is a greater ratio of former smokers among the elderly male physicians, as it has been already shown in other studies 8,13 . Most of the ENTs who stopped smoking (74%) did it on their own.…”
Section: Discussionsupporting
confidence: 67%
“…Non-smoking physicians had more unfavorable views towards smoking than those who smoked (Parna et al 2005b). Former smokers were more likely to indicate that their help in getting patients to quit was not effective compared to smokers (Josseran et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Health behaviors among doctors have been suggested to be an important marker of how harmful lifestyle behaviors are perceived. Thus, it has repeatedly been found that physicians who are smoking restrict from advising their patients to quit smoking cigarettes (Barengo et al 2005;Josseran et al 2005;Nardini et al 1998;Parna et al 2005a, b). Smoking physicians were also less likely to agree with statements that would change their current freedom to smoke cigarettes (Hodgetts et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…When the smoking rate of Turkish GPs were compared to that of their European colleagues, a higher rate was found. The smoking rate of Italian, German, French GPs and Swiss primary care physicians were reported to be 28.3, 32.1, 9.6 and 12%, respectively (Pizzo et al 2003;Twardella and Brenner 2005;Josseran et al 2005;Sebo et al 2007). The mean age for starting of smoking on a regular basis was 21 years, which means that most GPs started smoking during their medical education.…”
Section: Discussionmentioning
confidence: 99%